Mean values of the FPI thermospheric wind and Dynasonde ionospheric velocity in Tromsoe, Norway - 大山, 伸一郎; 20444424; Oyama, Shin-ichiro; orcid:0000-0002-5831-6134 (Geophysical Research Letters, 2023)
dataset